TL-Moments for Type-I Censored Data with an Application to the Weibull Distribution - Hager A. Ibrahim; Mahmoud Riad Mahmoud; Fatma A. Khalil; Ghada A. El-Kelany (Mathematical and Computational Applications, 2018)
This paper aims to provide an adaptation of the trimmed L (TL)-moments method to censored data. The present study concentrates on Type-I censored data. The idea of using TL-moments with censored data may seem conflicting. However, our perspective is that we can use data censored from one side and trimmed from the other side. This study is applied to estimate the two unknown parameters of the Weibull distribution. The suggested point is compared with direct L-moments and maximum likelihood (ML) methods. A Monte Carlo simulation study is carried out to compare these methods in terms of estimate average, root of mean square error (RMSE), and relative absolute biases (RABs).